Sociocultural Perspective in Law Enforcement on Drug Abuse in Donggala Regency Police Resort, Central Sulawesi - Lukman Lukman; Sulbadana Sulbadana; Hamdan Rampadio; Syachdin Syachdin (JURNAL AKTA, 2026)
Drug abuse has become a global threat affecting legal, social, health, and national security systems, requiring not only strict law enforcement but also comprehensive community participation to ensure effective prevention and control. This study aims to analyze the effectiveness of law enforcement in addressing drug abuse at the local level and to examine the role of law enforcement agencies in prevention efforts and suppression of drug abuse in Donggala District. The method applied a socio-juridical approach, which involved exploring existing regulations, such as Law Number 35 of 2009 on Narcotics, and relating them to the community’s social conditions through interviews, observations, and field studies. The findings indicate that law enforcement still faces challenges such as limited facilities and infrastructure, low public legal awareness, and weak supervision in coastal and border areas that serve as entry points for narcotics. As a novel contribution, this dissertation proposes the concept of a “Drug-Free Resilient Village” (Anti-Narcotics Resilient Village). This community-based model integrates education, early detection, social monitoring, and rehabilitation functions within a single area grounded in local wisdom. This model is expected to strengthen preventive approaches while enhancing the effectiveness of bottom-up law enforcement.